Factors that influence job satisfaction in Jabatan Ketua Menteri at Seri Negeri Melaka / Nurhudah Mohd Bashir (Faculty of Business and Management, 2007)
The purpose of this research is to study the factors that influence job satisfaction in Jabatan Ketua Menteri Melaka (JKMM) at Seri Negeri Melaka and the relationship between benefit, working environment and leadership with job satisfaction. Moreover, this study will examine and measure the level of job satisfaction in order to enhance and gain more satisfaction among the employees. In getting relevant data, 50 questionnaires were distributed to the employees in JKMM at Seri Negeri Melaka. The respondents were chosen as convenience sampling. Data collected were analyzed by using Statistical Package for Social Science (SPSS) program. The analysis includes the frequency, cross-tabulation and correlation. The findings showed factors that influence job satisfaction in JKMM are benefit and working environment. Thus, recommendations are included in this project paper in order to help JKMM to increase the satisfaction of their employees in order to achieve organisation goals.